Geração de trombina em cães com hiperadrenocorticismo endógeno - Mora, Silvia Eugenia Vargas (2020)
The hypercoagulable state is a serious condition that can lead to thrombosis and/or disseminated intravascular coagulation. Several diseases are associated with its development; however, conventional coagulation tests are unable to detect thrombotic risk. For the past few years, the thrombin generation test (TGA) has become one of the most studied methods for evaluating global hemostasis. Hyperadrenocorticism (HAC) is a common canine endocrinopathy that have been associated with hypercoagulability. However, the pathophysiological mechanisms are diverse and some of them are still misunderstood. The objective of this study was to evaluate the applicability of TGA for detecting compatible alterations with a hypercoagulable tendency and to correlate with an hemostatic profile comprised of fibrinogen, antithrombin (AT), D-dimer, prothrombin time (PT) activated partial thromboplastin time (aPPT), and routine laboratory tests for elucidating possible prothrombotic mechanisms. The majority of dogs (80.6%) presented at least one alteration of the hemostatic profile and/or TGA parameters. TGA at high concentration of activator showed significantly higher ETP (P= 0.0239) and peak (P= 0.0281) in Cushing patients. Fibrinogen (P = <0.0001) and AT (P = 0.0444) activity were significantly higher in the HAC group, while PT (P = 0.0046) and aPTT (P = 0.0002) were lower. Basal cortisol levels correlated positively with fibrinogen levels (r = 0.4503; P = 0.0355) and negatively with AT values (r = -0.4580; P = 0.0280). Fibrinogen and hematocrit values showed a negative correlation (r = -0.4853; P = 0.0076). Our study showed that dogs with HAC presented higher thrombin generation, however, TGA performed with lower concentrations of tissue factor were inadequate for assessing hypercoagulability. Degree of hypercortisolism influences AT and fibrinogen levels. Proteinuria does not appear to determine AT activity and dogs with HAC showed a significantly shortened PT and aPTT.